Hyperlactatemia Predicts Citrate Intolerance With Regional Citrate Anticoagulation During Continuous Renal Replacement Therapy. (May 2019) - Tan, Jia-Neng; Haroon, Sabrina Wong Peixin; Mukhopadhyay, Amartya; Lau, Titus; Murali, Tanusya M.; Phua, Jason; Tan, Zong-Yao; Lee, Nicholas; Chua, Horng-Ruey
Purpose: We aim to determine whether hyperlactatemia, which suggests multi-organ dysfunction and impaired organic substrate metabolism, may predict intolerance to regional citrate anticoagulation (RCA) during continuous venovenous hemofiltration (CVVH). Methods: We performed a single-center, retrospective observational study in critically ill patients with acute kidney injury or end-stage renal disease and evaluated the association of peak serum lactate levels with citrate intolerance (CI) during the initial 72 hours of RCA-CVVH, defined by serum total-to-ionized calcium >2.5 plus systemic hypocalcemia. Results: Eighty-eight patients were studied (aged 59 ± 14 years, 66% males, Acute Physiology and Chronic Health Evaluation II: 31 ± 8). Citrate was dosed at median 2.1 mmol/L of blood flow, with citrate load of 30 mmol/h, and CVVH effluent of 43 mL/kg/h. Twenty patients developed CI. Comparing patients with CI versus none, peak lactate levels were 8 (5-11) versus 3 (2-6) mmol/L, calcium replacement was 13 (10-17) versus 11 (8-12) mmol/h, and standard base excess was −4 (−12 to 1) versus 2(−4 to 7) mmol/L, respectively ( P < .05). Citrate intolerance developed in 38%, 44%, and 55%, in patients with peak lactate >4, >6, >7 mmol/L, respectively, versus 7% in those with peak lactate ≤4 mmol/L ( P ≤ .001), despite comparable citrate load and effluent rates across all categories. On multivariate analysis, hyperlactatemia and hyperbilirubinemia predicted CI ( P ≤ .01), which was associated with increasing calcium infusion requirement. Higher peak lactate from >4 to >7 mmol/L predicted CI with graded increase in odds ratio and specificity from 59% to 87%, but the corresponding negative predictive value from 93% to 87%. Area under nonparametric receiver operating characteristic curve for peak lactate and CI was 0.78. Conclusion: Hyperlactatemia predicts CI during RCA-CVVH with reasonable discriminatory performance in critically ill patients. Serum lactate surveillance may help preempt issues with citrate toxicity.